298. Dosimetric cardiac constraints for long-term cardiac mortality excess control during the tangential beams irradiation of the left breast. (December 2018) - Grimaldi, L.; Morandini, V.; Giancaterino, S.; Bonizzi, D.; Panese, A.; Saiani, F.; Berlinghieri, S.; Castrezzati, E.; Spiazzi, L.; Frata, P.
Abstract : Purpose: Careful evaluation of the heart-absorbed dose has to be adopted in any Radiotherapy Center and although a risk of cardiac death <1% after breast RT is considered acceptable, the QUANTEC constraint V 25 Gy < 10 % is not sufficient to limit the excess cardiac mortality risk for each patient and for every RT schedule of tangential beams left sided breast RT. Aim of this work is to find a group of patient for which the dose constraint, above mentioned, is respected, but at a further investigation the excess cardiac mortality probability results greater than 1%. Than a correlation between these results and the dose volume histogram (DVH) has to be investigated and verified on a control group of patients. Methods and materials: Analyzing the DVHs on TPS Philips Pinnacle 3 of 240 women, who underwent to left sided breast tangential beams RT, came out that the constraint V 25 Gy < 10 % was respected. By inspecting the integral DVHs some patients were individuated as "probable false negatives". The Relative Seriality model ( α / β = 3 Gy, s = 1, D 50 = 52.4 Gy and g = 1.28 ) was used as method to evaluate the probability of late cardiac mortality. Results: For 19 patients the V 25 Gy was satisfied, but the probability of long-term cardiac mortality was found > 1% and up to 6%. The dosimetric heart constraints V 40 Gy and D 2 % showed a good correlation (R = 0.97 and R = 0.90 respectively) with the risk of cardiac death. To keep the probability lower than 1%, the cut off levels were determined by the simultaneous occurrence of the conditions: V 40 Gy < 2 %, and D 2 % < 38 Gy . The generalized gEUD was also valuated with an a = 5.7 For all calculations considering the EQD2Gy dose correction was considered. Conclusions: This probability was only a calculation and not an observation of mortality. Anyway modern TPSs should promote, even more, the use of either radiobiological DVHs or algorithm optimization, especially in the era of hypofractionation.